THE INFLUENCE OF PRINCIPAL LEADERSHIP AND COMPETENCE ON WORK CULTURE AND ITS IMPLICATIONS ON THE PERFORMANCE OF PRINCIPAL TEACHERS IN PICUNG DISTRICT, PANDEGLANG REGENCY - Supriatin, Titin; Rustandi, Tata; Permana, Angrian (Yayasan Education and Social Center, 2025)
The low teacher work culture, weak principal leadership, and suboptimal principal competency are the background of this study because these conditions affect teacher performance. The main focus of this study is to examine the influence of principal leadership and competency on work culture, and its impact on teacher performance. The research approach used is quantitative with a survey method. The research subjects included 205 public elementary school teachers in Picung District, Pandeglang Regency, with a sample of 135 people determined using a proportional technique. Data were collected using a Likert-based questionnaire instrument, then analyzed through regression with the help of SmartPLS software. Research findings show that principal leadership has a positive and significant influence on both work culture and teacher performance. Similarly, principal competence has been shown to have a positive and significant impact on both work culture and teacher performance. Furthermore, work culture serves as a mediating variable, strengthening the relationship between principal leadership and competence and improved teacher performance. It can be concluded that the more effective the leadership and the more optimal the principal's competence, the better the work culture developed among teachers. Ultimately, this condition encourages improved teacher performance and contributes to higher quality education.